2021
DOI: 10.1016/j.fas.2020.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Validity of five foot and ankle specific electronic patient-reported outcome (ePRO) instruments in patients undergoing elective orthopedic foot or ankle surgery

Abstract: Validity of five foot and ankle specific electronic patient-reported outcome (ePRO) instruments in patients undergoing elective orthopedic foot or ankle surgery Uimonen, Mikko Elsevier BV Tieteelliset aikakauslehtiartikkelit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…This may indicate problems when evaluating the change over time. A study by Uimonen et al presented the modified LEFS with unsatisfactory convergent validity compared to 4 other foot and ankle PROMs (FAAM, FAOS, MOXFQ, VAS-FA) and to a general HRQL assessment using the EQ-5D (12). The authors hypothesized that the lack of general quality of life items in the LEFS leads to more function focused assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may indicate problems when evaluating the change over time. A study by Uimonen et al presented the modified LEFS with unsatisfactory convergent validity compared to 4 other foot and ankle PROMs (FAAM, FAOS, MOXFQ, VAS-FA) and to a general HRQL assessment using the EQ-5D (12). The authors hypothesized that the lack of general quality of life items in the LEFS leads to more function focused assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, test-retest reliability of the LEFS instrument has been reported as high (10,11). However, its convergent validity and distribution of scores in different patient groups have been criticized (12). Factor analyses have presented LEFS with loading on 2 or more factors (8,9,13,14).…”
mentioning
confidence: 99%
“…Patients were recruited to the study face-to-face or via mail before surgery. Patients completed the validated Finnish version 9 of VAS-FA either electronically on a tablet computer, or as a paper-and-pen version 15 .…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores indicate a higher level of functional status in each of the 2 subscales (2). Previous research suggests that the electronic version of the Finnish version of the FAAM has satisfactory construct validity, coverage, and targeting of the scales in electively operated foot and ankle patients (14).…”
Section: Faammentioning
confidence: 99%
“…Patient-reported outcome measures (PROMs) should be chosen according to their measurement properties, which include reliability, validity, and repeatability (13). Previous studies have shown FAAM to be a reliable instrument for the evaluation of several foot and ankle pathologies, with both good content and construct validity and responsiveness (2,4,14). Additional evidence in support of the construct validity of the FAAM has been provided for chronic ankle instability (5,6).…”
mentioning
confidence: 99%